4. Application of the FMECA analysis in breast radiotherapy with active breath hold. (December 2018) - Menegotti, L.; Vanoni, V.; Tomio, L.; Mussari, S.; Maino, M.; Valentini, A.; Mattiuzzi, C.; Martignano, A.
Abstract : Purpose: The Deep Inspiration Breath Hold (DIBH) technique was introduced in order to freeze the breathing motion in a mid-inhale position with a computer controlled valve, with the purpose of lowering heart dose in left breast radiotherapy. A training project with FMECA analysis was started, aiming to write and implement a protocol, improved by proactive clinical risk analysis and feedback from the operators (radiotherapists, radiographers and medical physicists). Methods and materials: At first, few operators were involved to take knowledge and dexterity with the system. They became the tutors and the core of the improvement group for the subsequent training project. The project was comprised of four stages: (1) implementation of the technique (tutors); (2) field training (tutors and operators); (3) training course on FMEA/FMECA analysis (all operators and clinical governance department); (4) implementation of the FMECA analysis in left breast radiotherapy DIBH treatments (tutors and FMEA-workgroup; the FMEA workgroup consisted of these professional roles: radiotherapists, radiographers, medical physicists and clinical governance area's physicians). Results: The outputs for each stage were: (1) redact the protocol and the training checklist; (2) training of all operators and application of the self-evaluation checklist; (3) understanding the clinical risk principles; (4) application of the FMEA analysis, data processing and final report. The self-evaluation checklist was comprised of 37 targets, with achieved/partially-achieved/not-achieved check boxes. The FMEA table was comprised of 48 activities, subdivided in 5 phases (DIBH-suitable-patients detection, treatment simulation, planning, radiotherapy treatment delivery, quality control), with pertinent Risk Probability Numbers associated. Points 1–3 were completed, while completion of point 4 is expected for the first half of 2018. Conclusion: The application of the FMEA/FMECA method allowed us to introduce proactive methods to analyze and manage the clinical risk related to the introduction of the new DIBH technique. The FMEA/FMECA method was included in a training project which allowed to obtain feedback from all the involved operators, improving the understanding of the work process, the skill and safety in the practical use and the redaction of a multidisciplinary protocol.